2014
DOI: 10.1098/rstb.2012.0510
|View full text |Cite
|
Sign up to set email alerts
|

Space in the brain: how the hippocampal formation supports spatial cognition

Abstract: Over the past four decades, research has revealed that cells in the hippocampal formation provide an exquisitely detailed representation of an animal's current location and heading. These findings have provided the foundations for a growing understanding of the mechanisms of spatial cognition in mammals, including humans. We describe the key properties of the major categories of spatial cells: place cells, head direction cells, grid cells and boundary cells, each of which has a characteristic firing pattern th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
354
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(371 citation statements)
references
References 213 publications
7
354
1
2
Order By: Relevance
“…The spatial view of hippocampal function was born out of the discovery of "place cells"-hippocampal neurons that fire when an animal moves through specific locations in an environment (O'Keefe and Dostrovsky, 1971). Subsequent studies have identified other types of spatial firing patterns of neurons in the neighboring entorhinal cortex and other areas, supporting the view that the hippocampal system creates maps of physical space and performs navigational computations (Moser et al, 2008;Hartley et al, 2014). Consensus between the memory and spatial views has been difficult because of differences in the species and approaches used-most experiments on memory involve the examination of declarative memory in humans, whereas most experiments on spatial cognition involve maze behavior in animals.…”
Section: Introductionmentioning
confidence: 86%
“…The spatial view of hippocampal function was born out of the discovery of "place cells"-hippocampal neurons that fire when an animal moves through specific locations in an environment (O'Keefe and Dostrovsky, 1971). Subsequent studies have identified other types of spatial firing patterns of neurons in the neighboring entorhinal cortex and other areas, supporting the view that the hippocampal system creates maps of physical space and performs navigational computations (Moser et al, 2008;Hartley et al, 2014). Consensus between the memory and spatial views has been difficult because of differences in the species and approaches used-most experiments on memory involve the examination of declarative memory in humans, whereas most experiments on spatial cognition involve maze behavior in animals.…”
Section: Introductionmentioning
confidence: 86%
“…Additional data does, indeed, support a significant role of the human hippocampal system in mediation of spatial orientation and related memory and cognition in general (e.g. Baumann and Mattingley 2014, Kaplan et al 2014, Boccia et al 2014, Ekstrom et al 2014, Hartley et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, for example, the space is encoded by "retinotopic" coordinates, in the parietal cortex the spatial coding is egocentric: its reference is the body of the observer. In hippocampus, spatial coding is allocentric, as a in a map (Hartley, Lever, Burgess, & O'Keefe, 2014). We ignore, for the most part, how the brain coordinates all these spaces and uses them to change the point of view.…”
mentioning
confidence: 99%